The Photograph - Graham Clarke (New York Oxford University Press, 1997)
How do we read a photograph? In this rich and fascinating work, Graham Clarke gives a clear and incisive account of the photograph's historical development, and elucidates the insights of the most engaging thinkers on the subject, such as Roland Barthes and Susan Sontag. From the first misty heliograph taken by Joseph Nicephore Niepce in 1826 to the classic compositions of Cartier-Bresson and Alfred Steiglitz and the striking postmodern strategies of Robert Mapplethorpe, Clarke provides a groundbreaking examination of photography's main subject areas--landscape, the city, portraiture, the body, and reportage--as well as a detailed analysis of exemplary images in terms of their cultural and ideological contexts. With over 130 illustrations, The Photograph offers a series of discussions of major themes and genres providing an up-to-date introduction to the history of photography and creating a record of the most dazzling, penetrating, and pervasive images of our time.
Keywords: Art; Nonfiction; Photography